YOUTH AND POLITICS – A THEORETICAL AND HISTORICAL STUDY - R., Girija (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This paper discusses the theories on youth and the history of youth politics. Generation categories are explained here. They are Revolutionary youth, Bohemian youth, Activist youth, Conformist youth, Reactionary youth, and Delinquent youth. Revolutionary youth are highly active politically, although only in limited ways. Their ideology states that progressive social changes can only be achieved through a radical social transformation. Bohemian youth generally share the revolutionaries' attempts for the social institutions of the dominant society, but they are suspicious of the solutions offered by the revolutionaries. Activist youth consequently work largely within accepted political channels, often concentrating their efforts on one particular issue or limiting their activities to political campaign periods. Conformist youth are politically withdrawn due to apathy, indifference, or satisfaction with the status quo. The reactionaries have many things in common with the revolutionaries. Delinquent youth admire strength and power and reject the existing authority figures. The socialization theory emphasizes the family as being the most important mechanism in political value socialization. Generation unit theory argues that youthful activism is age-linked. In the historical part contains student and youth politics in the U.S.A, Britain, France, Germany, Italy, Spain, Scandinavian countries and Japan. It also deals with student politics in socialist countries and India.